การสกัดตะกั่วจากกากแร่สังกะสี (Hot acid leach cake) โดยการละลายด้วยสารละลายโซเดียมคลอไรด์ - จิราภรณ์ จันสด (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
This research work was conducted to extract lead from hot acid leach (HAL) cake of zinc plant in Tak province by using sodium chloride solution. The variables studied were temperature (20 to 80 degrees Celsius), concentration of sodium chloride (100 to 300 g/l) and hydrochloric acid (0.1 to 0.5 mol/l ) and the amount of the HAL cake in leaching solution (10 to 80 g/l). The experimental results indicated that lead extraction increased with the increase of temperature and sodium chloride concentration. Lead could be totally extracted from the HAL cake containing approximately 25 % lead using sodium chloride concentration of 300 g/l and the amount of HAL cake up to 40 g/l at room temperature within one hour. Increasing the amount of HAL cake led to the decrease in lead extraction. When using 80 g/l of HAL cake only 79.78 % of lead could be extracted. However, when the hydrochloric acid concentration was increased to 0.5 mol/l and the temperature was increased to 80 degrees Celsius the lead extraction of 86.13 % and 95.14 % was achieved respectively.